The Sexual Dimorphism of the Neuroimmune Response in the Brains of Taenia crassiceps-Infected Mice - Karen Elizabeth Nava-Castro; Diana Lizeth Ruiz-Antonio; María del Sol Ríos-Avila; Claudia Angélica Garay-Canales; Lenin Pavón; Romel Hernandez-Bello; Víctor Hugo Del Río-Araiza; Manuel Iván Girón-Pérez; Jorge Morales-Montor (Brain Sciences)
Background: Helminth infections are associated with cognitive deficits, especially in school-age children. Deworming treatment in heavily infected children improves their short- and long-term memory recall. In mice, intraperitoneal helminth infection with Taenia crassiceps (T. crassiceps) shows sexual dimorphism in terms of the parasite load, immune response, hormone levels, and behavioral changes. We have previously shown poorer short-term memory performance and changes in the concentrations of cytokines and neurotransmitters in the hippocampus, which were replicated in this study. The molecular changes in other brain structures, such as those related to reproduction, are unknown. Methods: Male and female Balb/cAnN mice were chronically infected with T. crassiceps larvae. We determined the peritoneal parasite load and established the presence of cytokines and neurotransmitters in the hippocampus, olfactory bulb, and hypothalamus. Results: The parasite load was higher in female than male infected mice, as expected. In the hippocampus, the neurotransmitters norepinephrine and serotonin increased in males but decreased in females. In contrast, in the olfactory bulb and hypothalamus, the neurotransmitters assessed showed no statistical differences. The cytokine profiles were different in each brain structure. The TNF-α levels in the olfactory bulb and the IL-4 levels in the hippocampus of infected mice were dimorphic; IFN-γ was augmented in both male and female infected animals, although the increase was higher in infected males. Conclusions: The brain responds to peripheral infection with cytokine levels that vary from structure to structure. This could be a partial explanation for the dimorphic behavioral alterations associated with infection, it also demonstrates the synergic interaction between the immune, the endocrine, and the nervous systems.